Cognitive And Cultural Dimensions Of Urban Micro toponyms: A Cross-Cultural Analysis Of Tashkent And London (Zien Journal of Social Sciences and Humanities, 2026)
This study offers a comparative analysis of the microtoponymic systems of Tashkent and London within cognitive linguistics and linguocultural frameworks. It investigates how urban place names function as cognitive and cultural markers encoding collective memory, social identity, and spatial perception. The corpus includes 150 microtoponyms from central and peripheral districts of both cities. Using semantic classification, etymological analysis, and cognitive mapping, the study categorizes naming motivations and examines underlying conceptual structures. Findings show that Tashkent’s microtoponyms reflect ideological dynamism, multilingual layering, and shifting national identity, while London’s demonstrate historical stability and continuity tied to trade and heritage. Both systems share universal cognitive mechanisms such as anthropocentric naming and metaphorical representation. The study concludes that microtoponyms serve as cognitive maps linking language, culture, and urban space, contributing to urban semiotics and onomastics.